Arthroscopic Pancapsular Shift With Labral Repair for Multidirectional Instability of the Shoulder - Frangiamore, Salvatore J. (Arthrosc Tech, 2017)
Initial treatment of shoulder multidirectional instability (MDI) consists of nonoperative modalities of physical therapy and rehabilitation; if this fails, surgical treatment can become necessary. MDI of the shoulder can be challenging to manage in individuals who fail conservative management. Historically, surgical treatment for MDI has been open capsular plication; however, arthroscopic capsular plication has now become the standard of care, with outcomes similar to the open procedure. The purpose of this article and Video 1 is to describe our arthroscopic technique for pancapsular shift with labral repair.